Damage models of composite materials - Demeshko, Yaroslav; Bobyr, Mykola (Mechanics and Advanced Technologies, 2025)
An analysis of modern damage models and failure criteria for composite materials (CM) at the stage of macrocrack initiation is performed and the limits of their application are determined. The classification of CMs, as well as the main hypotheses and assumptions used to construct equations of state are considered. Particular attention is paid to the stage of initiation and accumulation of scattered damage at the micro- and meso-levels as a key phase of the life cycle of a CM product. The concepts of continuum damage mechanics, thermodynamics of irreversible processes, and mechanics of a solid deformable body are applied. The relevance of the work is due to the growing requirements for the reliability and durability of CM structures, especially in the aviation, automotive, and construction industries. Despite significant progress in research, there is a need to improve damage models that take into account complex micro- and mesoscale fracture processes. The methods of continuum damage mechanics, thermodynamics of irreversible processes, and deformable body mechanics are applied. Phenomenological and micromechanical models of damage are considered, which describe the accumulation of damage in the matrix, reinforcing fibers, and interfaces. The main mechanisms of microfracture in reinforced CMs are described, including damage to the matrix, reinforcing fibers, and the interface between them. The necessity of taking into account a set of phenomenological parameters to describe the kinetics of damage accumulation is demonstrated. It is noted that complex processes in reinforced CMs require phenomenological modeling of damage with the use of tensor quantities and certain assumptions, particularly the “mixture” hypothesis. The expediency of using the hypothesis of equivalence of specific energies to determine the components of the damage parameter is confirmed